Pseudo Primary Aldosteronism as Initial Presentation of Ectopic ACTH Syndrome in Metastatic Small Cell Lung Cancer. Issue 1 (30th November 2022) - Shakesprere, Jonathan; El Naili, Reima; Sadiq, Mehjabeen; Haider, Adnan
Abstract: Ectopic adrenocorticotropic hormone (ACTH)-secreting syndrome (EAS) is a rare but often aggressive paraneoplastic syndrome. Patients with EAS typically present with high ACTH levels and rapid clinical progression in the setting of acute cortisol elevation, which can delay diagnosis due to a lack of typical Cushingoid features. High levels of ACTH have also been shown to stimulate the adrenal zona glomerulosa to oversecrete aldosterone. We present the case of a 58-year-old male individual presenting with new-onset hypertension and severe metabolic alkalosis with spontaneous hypokalemia, in the setting of elevated aldosterone and low renin levels, suggestive of primary aldosteronism. Subsequent biochemical testing, imaging, and pathology, however, revealed suppression of aldosterone with evidence of hypercortisolism in the setting of metastatic small cell lung cancer. This was, therefore, suggestive of pseudo primary aldosteronism in the setting of a paraneoplastic ectopic ACTH-producing syndrome. This case highlights that hypercortisolism, in the setting of EAS, can initially present with a clinical picture suggestive of hyperaldosteronism. The use of a dexamethasone suppression test can allow the clinician to differentiate between idiopathic bilateral adrenal hyperplasia and ectopic ACTH syndrome.